Sovereignty demands constant vigilance and the readiness to defend it. - Święczkowski, Bogdan (A thousand years of Poland’s presence among the elite of European states, 2026)
Bogdan Święczkowski, President of the Constitutional Tribunal, welcomes the attendees and outlines the significance of the coronation of Bolesław the Brave in 1025 as an event that confirmed Poland's belonging to the Western civilizational sphere and its standing as an equal among the sovereign monarchies of Europe. Święczkowski emphasizes that sovereignty is not a value granted once and for all, but one that requires constant vigilance and the readiness to defend it. In this context, he points to the particular role of the Constitutional Tribunal as the guardian of the Constitution and of the state's institutional independence. He notes that in the face of the challenges posed by globalization, cultural conflicts, and the redefinition of sovereignty within the European Union, the defense of Poland's constitutional identity takes on special importance — not as isolation, but as a partnership-based coexistence within a Europe of nations. The address concludes with a call to the attendees — historians, lawyers, philosophers, and public figures — for the debate to become a meaningful contribution to the broader discussion on sovereignty and Poland's place in Europe. The legacy of the first royal coronation is to serve not only as a source of national pride, but also as an obligation to maintain Poland's standing among Europe's leading states through responsible decision-making and fidelity to the principles that underpin statehood.